2012
DOI: 10.1142/s2010132511300023
|View full text |Cite
|
Sign up to set email alerts
|

Ways of Next Generation Refrigerants and Heat Pump/Refrigeration Systems

Abstract: Since measures of the global warming are becoming urgent issues, various technical innovations and social system reformations are being promoted. In the engineering fields of heating, refrigerating, and air-conditioning, the global warming caused by the refrigerants is a big problem that must be solved. At the present stage, however, there are no perfect solutions for next generation refrigerants and heat pump/refrigeration systems by which the global warming is successfully prevented. Therefore, we have to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The use of refrigerants with high Global Warming Potential (GWP) and Ozone Depletion Potential (ODP), which contribute cardinally to global warming and thereby affect people's health, has become an attention-grabbing issue. Some restrictions and prohibitions on the use of refrigerants have been introduced through decisions made due to international agreements and policies, such as the F-gas Regulation, the Kyoto Protocol, the Montreal Protocol and the Paris Agreement [3]. Chlorofluorocarbons (CFCs), a part of the most common first-generation refrigerant group and among the substances that destroy the ozone layer, were the first prohibited refrigerants [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The use of refrigerants with high Global Warming Potential (GWP) and Ozone Depletion Potential (ODP), which contribute cardinally to global warming and thereby affect people's health, has become an attention-grabbing issue. Some restrictions and prohibitions on the use of refrigerants have been introduced through decisions made due to international agreements and policies, such as the F-gas Regulation, the Kyoto Protocol, the Montreal Protocol and the Paris Agreement [3]. Chlorofluorocarbons (CFCs), a part of the most common first-generation refrigerant group and among the substances that destroy the ozone layer, were the first prohibited refrigerants [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…5A, pp. -2989 ly used in small heat pump and refrigeration systems since they have excellent thermodynamic properties and applicability employed in the system equipment's [3][4][5]. More than 85% of refrigerator producers in China depend on R600a which is thoroughly commanding refrigerant in numerous countries.…”
Section: Introductionmentioning
confidence: 99%
“…Test results showed that time taken to form ice cream using the refrigerant mixture R290/RE170 (65/35 by mass %) was less compared to R404A and also its COP was better compared to R404A. Simulation studies were done with refrigerant mixtures like R744/RE170 and R1234ze(E)/R32 in order to exhibit possible ways to use these refrigerants as next generation refrigerants in the heat pump and refrigeration sectors [10].…”
Section: Introductionmentioning
confidence: 99%